Association between lifestyle and skin moisturizing function in community-dwelling older adults - Ryosuke Oizumi; Rie Shibata (PAGEPress Publications, 2024)
The skin moisturizing function decline with age, leading to skin dryness in approximately 40% of the olderly. Various lifestyle habits may affect the skin moisturizing function, however it is not clear which ones are particularly relevant. A cross-sectional study was conducted between September and December 2023, involving individuals aged 65 years and older. Self-administered questionnaire were employed to collect information on lifestyle habits. Stratum corneum hydration (SC hydration), as an indicator of skin hydration, was measured and analyzed using multiple regression. A total of 124 individuals participated in the study, with a mean age of 83.6 years. Daily use of moisturizer (p=0.024) and activity level (p=0.002) demonstrated significant associations with increased SC hydration. Although not statistically significant, smoking exhibited a trend towards decreased SC hydration (p=0.173). The findings of this study suggest that, among various lifestyle habits, exercise and daily moisturizing contribute to enhanced SC hydration. These results suggest that lifestyle modifications may improve the skin moisturizing function of olderly.